KUALITAS PELAYANAN KESEHATAN RAWAT INAP DI PUSKESMAS BANYUANYAR SURAKARTA Studi Kasus Pasien Miskin Pengguna Badan Penyelenggara Jaminan Sosial - Joko Suranto, Hanjar Adhi Prastyawan, Joko Pramono & (Transformasi, 2017)
This research aims to analyze the quality of inpatient health services at Clinics Banyuanyar CitySurakarata. The theory used in the study, namely the theory put forth by Lupiyoadi. The theoryis used as a determinant of the quality of health care in health centers stay rawap Banyuanyaralready good or not. Indicators to measure the level of success in providing services is locatedon five dimensions of service quality that is the physical ketampakan, reliability, responsiveness,assurance, and empathy. Based on the results of the research of service quality of inpatient careat Clinics Banyuanyar's been good. From the results of the study it can be concluded that inGeneral from the five dimensions that is direct evidence, reliability, responsiveness, assuranceof service quality of empathy, of health in the health Banyuanyar Surakarta votes quite well. Ofthe five dimensions that there are some who need to be a concern, namely in terms of the narrowparking lot, the lack of four-wheeled vehicles create parking and narrow waiting room, thereare some officers who still often health centers come late, Readiness officer in dealing with thecomplaints of the patient.Key words: Tangibles, Reliability, Responsiveness, Assurance, Empathy